The use of Mindfulness Acceptance Commitment (MAC) approach for Malaysian elite triathletes - Koh, Eugene Boon Yau; Pang, Nicholas Tze Ping; Kuan, Garry (Routledge, 2021)
Mindfulness Acceptance Commitment (MAC) approach has been introduced into the sport psychology field and has shown a lot of interest in the applied practices. Athletes who receive MAC approach are taught to deal with challenging internal experiences in a non-judgmental way, choosing to persist with their task-at-hand despite discomforts and to remain focused on being grounded at the present moment. In Malaysia, the elite triathletes have not been exposed to the MAC approach before. This paper aims to describe how the MAC approach was provided to the Malaysian elite triathletes. MAC was taught over six weeks, with one MAC theme introduced per week. Each triathlete was given a one-on-one session of 60-90 minutes per week with homework and practical exercises. After six weeks, the triathletes reported marked improvement in their sport and additional improvements in other domains of their life. Considering the promising improvements of the elite triathletes who received the MAC approach, it is worth considering that the MAC approach should be adapted and incorporated into the triathlon sport.